Clinical Validation of a Sound Processor Upgrade in Direct Acoustic Cochlear Implant Subjects. Issue 5 (June 2017) - Kludt, Eugen; D'hondt, Christiane; Lenarz, Thomas; Maier, Hannes
Abstract : Objective: The objectives of the investigation were to evaluate the effect of a sound processor upgrade on the speech reception threshold in noise and to collect long-term safety and efficacy data after 2½ to 5 years of device use of direct acoustic cochlear implant (DACI) recipients. Study Design: The study was designed as a mono-centric, prospective clinical trial. Setting: Tertiary referral center. Patients: Fifteen patients implanted with a direct acoustic cochlear implant. Intervention: Upgrade with a newer generation of sound processor. Main Outcome Measures: Speech recognition test in quiet and in noise, pure tone thresholds, subject-reported outcome measures. Results: The speech recognition in quiet and in noise is superior after the sound processor upgrade and stable after long-term use of the direct acoustic cochlear implant. The bone conduction thresholds did not decrease significantly after long-term high level stimulation. Conclusions: The new sound processor for the DACI system provides significant benefits for DACI users for speech recognition in both quiet and noise. Especially the noise program with the use of directional microphones (Zoom) allows DACI patients to have much less difficulty when having conversations in noisy environments. Furthermore, the study confirms that the benefits of the sound processor upgrade are available to the DACI recipients even after several years of experience with a legacy sound processor. Finally, our study demonstrates that the DACI system is a safe and effective long-term therapy.